Analysis of Planting Distance in the Cultivation of Cavendish Banana Plants in Petani Desa (pEdE) Durungbedug, Candi Sidoarjo : Analisa Jarak Tanam Pada Budidaya Tanaman Pisang Cavendish di Petani Desa (pEdE) Durungbedug Candi Sidoarjo - Alifiansyah Putra, Muhammad; Abror, M (Procedia of Engineering and Life Science, 2025)
The purpose of this internship was to analyze the effect of planting distance on the vegetative growth of Cavendish banana plants (Musa acuminata AAA group) on the farmland of Petani Desa (pEdE) Durungbedug, Candi, Sidoarjo. Planting distance is an important factor in banana cultivation because it affects the availability of growing space, nutrient absorption, light intensity, and land use efficiency. This internship used an observational-participatory method with three planting distance treatments: 1.5 x 1.5 meters, 2 x 2 meters, and 2.5 x 2.5 meters. The observed parameters included plant height, number of leaves, and pseudostem diameter during the observation period of approximately 2 months. The results showed that a planting distance of 2 x 2 meters produced the best growth, with an average plant height of 145 cm, 9 leaves, and a pseudostem diameter of 21 cm. The planting distance of 1.5 x 1.5 meters showed stunted growth due to interplant competition, while the distance of 2.5 x 2.5 meters provided The growth is quite good but less efficient in terms of land productivity. Based on these results, a planting distance of 2 x 2 meters is recommended as the optimal spacing for cultivating Cavendish bananas under environmental conditions with medium–high rainfall and good fertilization management. Keywords: Cavendish banana, planting distance, vegetative growth, land efficiency, banana cultivation